Analisis Kenaikan Harga Beras Terhadap Mahasiswa Universitas Negeri Semarang - Anastasia Retno; Istinaroh Hairun Nisa; Lidwina Nathania (KIRANA : Social Science Journal, 2024)
Rice is the main food need of the Indonesian people. The price of rice in Gunung Pati, Semarang has increased to touch Rp. 18,000.00/ kilogram. The increase in rice prices at the beginning of 2024 is a serious problem that must be addressed immediately. The purpose of this study is to analyze the factors that influence the increase in rice prices, the impact on society, and find solutions. The methods used are quantitative, literature studies, and government data. This article data collection technique is through questionnaires and literature studies through books, articles, and several scientific journals. The result of this study is the increase in rice prices caused by the natural phenomenon of El Nino, floods, and crop failure. To address this issue requires a comprehensive effort from the government, private sector, and society. From this study, it can be concluded that the increase in rice is a complex problem and greatly affects economic stability.